2016
DOI: 10.3177/jnsv.62.402
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Linolenic Acid-Enriched Diacylglycerol Oil Suppresses the Postprandial Serum Triglyceride Level—A Randomized, Double-Blind, Placebo-Controlled, Crossover Study

Abstract: SummaryThis study investigated the effect of a single oral ingestion of alpha-linolenic acid-enriched diacylglycerol (ALA-DAG) on postprandial serum triglyceride (TG) levels. A randomized, double-blind, controlled, crossover study was performed in subjects with normal or moderately high fasting serum TG levels. Subjects ingested 0.00 g [control: triacylglycerol; TAG (rapeseed oil)], 1.25 g (1.25-g: mixture of 1.25 g ALA-DAG and 1.25 g TAG), or 2.50 g (2.50 g) of ALA-DAG in random order with a 6-d washout perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A trial showed that ALA‐rich diglyceride (2.5 g/day) reduced the postprandial serum TG level in 38 subjects with normal and moderately high fasting serum TG levels. However, their trial showed that low‐dose ALA‐rich diglyceride (1.25 g/day) had no therapeutic effect (Yamanaka et al, 2016). A 4‐week trial showed that ALA‐rich diglyceride (2.5 g/day) reduced visceral fat area and increased fat oxidation in 17 normal and moderately obese subjects (Ando, Saito, Miura, Osaki, & Katsuragi, 2017).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…A trial showed that ALA‐rich diglyceride (2.5 g/day) reduced the postprandial serum TG level in 38 subjects with normal and moderately high fasting serum TG levels. However, their trial showed that low‐dose ALA‐rich diglyceride (1.25 g/day) had no therapeutic effect (Yamanaka et al, 2016). A 4‐week trial showed that ALA‐rich diglyceride (2.5 g/day) reduced visceral fat area and increased fat oxidation in 17 normal and moderately obese subjects (Ando, Saito, Miura, Osaki, & Katsuragi, 2017).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…A trial showed that ALA‐rich diglyceride (2.5 g/day) reduced the postprandial serum TG level in 38 subjects with normal and moderately high fasting serum TG levels. Low‐dose ALA‐rich diglyceride (1.25 g/day) had no therapeutic effect (Yamanaka et al, 2016). Another trial showed that both high‐dose ALA (3.4 g/day) and low‐dose ALA (0.9 g/day) could improve vascular function and inflammation in 81 overweight‐to‐obese patients with metabolic syndrome by decreasing the expression of CRP, TNF‐α, IL‐6, sICAM‐1, sE‐selectin, YKL‐40, and asymmetric dimethylarginine (Cavina et al, 2021; Egert et al, 2014).…”
Section: The Effect Of the Dose Is Not Negligiblementioning
confidence: 99%
See 1 more Smart Citation
“…74,75 Similarly, Egert et al 76 reported that serum TG levels significantly decreased after ALA intervention in normolipidemic individuals. Furthermore, Yamanaka et al 77 reported in a randomised, double-blind, controlled crossover study that a single oral ingestion of ALA-rich diacylglycerol oil suppressed postprandial serum TG levels in humans. These results suggest that the decrease in serum TG levels observed in both the PO and POAC groups after 12 months of treatment was caused by the increased ALA intake.…”
Section: Food and Function Papermentioning
confidence: 99%
“…In food products especially monoacylglycerols and diacylglycerols (MAG and DAG, respectively) are frequently used due to their facile delivery to the human body and the simple processability of these compounds in the dietary products. Some very recent studies showed that α‐linolenic acid‐rich diacylglycerol has promising health promotion functions especially in reduction of visceral fat area (VFA), BMI and serum triacylglycerol (TAG) in men and women with overweight (Ando et al, ; Saito, Fukuhara, Osaki, Nakamura, & Katsuragi, ; Saito, Mori, Osaki, & Katsuragi, ; Yamanaka et al, ). Research showed that DAG activated enzymes involved in β‐oxidation in the liver and small intestine (Murase et al, ; Murase, Aoki, Wakisaka, Hase, & Tokimitsu, ).…”
Section: Introductionmentioning
confidence: 99%